On the question of the acquisition of literary texts and the method of their processing for the needs of independent literary research - Změlík, Richard (Bohemistyka, 2025)
The study deals with the issue of acquisition of digital literary data, specifically prose texts of Czech literature, which the data would serve for independent scientific research in the context of digital humanities, or computational literary studies. In the first part, we focus on selected available foreign textual databases, which we characterize with respect to the stated goal, i.e. to the existence of such a digital data collection that would be internally structured and machine-readable. We then focus on the Czech environment, in the context of which we present the emerging database of prosaic texts of Czech literature. We describe its basic structure, the advantage of such structuring, and concrete examples of possible use of the database in statistical analysis of literary texts. We conclude that in the context of the current development of DH we can expect an increasing demand not only for specialized web applications of digital literary corpora, but especially for access to such or similar databases, as these allow for highly variable and individual research.